Changes in The Number of Mold and Acceptance Rate of Kappaphycus alvarezii Jelly Candy Packed with Edible Film Gelatin-CMC During Storage - Naiu, Asri Silvana; Yusuf, Nikmawatisusanti; Hudongi, Yusnina (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
This study aimed to analyze changes in the number of molds and the level of panelist acceptance of K. alvarezii jelly candy packaged using gelatin-CMC edible film during storage. The method used in this study is a laboratory experimental method which consists of two stages, namely preliminary research which aims to determine the best edible film formula to be used as jelly candy packaging and the main research to analyze changes in the number of molds and the level of acceptance of appearance, taste, aroma and texture of jelly candy that has been packaged using a gelatin-CMC edible film during storage. Storage for 60 days was converted to 15 days in a climatic chamber with a temperature of 40 ℃ and a humidity of 75%. Sampling was carried out every 3 days. The research design used linear regression to see the relationship between storage time and test parameters. The results of the preliminary study showed the best formula for edible film, namely 1% gelatin, 0.3% bees wax, 0.75% CMC, and 0.3% glycerol which resulted in a water vapor transmission rate of 18.60 g/m2/24 hours. The results of the main study showed that storage time had a moderate effect on mold. Mold was detected on the last day of observation, storage time had a very strong effect on the level of acceptance which decreased with storage time. The organoleptic value of jelly candy packaged using gelatin-CMC edible film was still acceptable to the panelists until the 36th day of storage.